Quantitative histological grading methods to assess subchondral bone and synovium changes subsequent to medial meniscus transection in the rat. (4th May 2017) - Kloefkorn, Heidi E.; Allen, Kyle D.
ABSTRACT: Aim of the Study: The importance of the medial meniscus to knee health is demonstrated by studies which show meniscus injuries significantly increase the likelihood of developing osteoarthritis (OA), and knee OA can be modeled in rodents using simulated meniscus injuries. Traditionally, histological assessments of OA in these models have focused on damage to the articular cartilage; however, OA is now viewed as a disease of the entire joint as an organ system. The aim of this study was to develop quantitative histological measures of bone and synovial changes in a rat medial meniscus injury model of knee OA. Materials and Methods: To initiate OA, a medial meniscus transection (MMT) and a medial collateral ligament transection (MCLT) were performed in 32 male Lewis rats (MMT group). MCLT alone served as the sham procedure in 32 additional rats (MCLT sham group). At weeks 1, 2, 4, and 6 post-surgery, histological assessment of subchondral bone and synovium was performed (n = 8 per group per time point). Results: Trabecular bone area and the ossification width at the osteochondral interface increased in both the MMT and MCLT groups. Subintimal synovial cell morphology also changed in MMT and MCLT groups relative to naïve animals. Conclusions: OA affects the joint as an organ system, and quantifying changes throughout an entire joint can improve our understanding of the relationship between joint destruction and painful OA symptoms following meniscus injury.